An examination of the reporting mechanism under section 6 of the employment act 2007: barriers to reporting sexual harassment in the workplace - Nyaga, Brian Kelly (Strathmore University, 2020)
Sexual harassment in the workplace refers to any unwanted sexual attention by employers or colleagues which impedes performance in a place of employment. It has proven to be a prevalent challenge to reasonable working conditions in Kenya. The hypothesis proposes that a significant relationship exists between the structure of the reporting mechanism under section 6 of the Employment Act and the reluctance displayed by victims in using it. Against this background, the study explores the relationship between the structure reporting mechanism in the Employment Act and the willingness of victims to report. The study has been informed by the dominance feminism theory that identifies dominance as the basis for sexual harassment. Results drawn from studies and case law surrounding sexual harassment in Kenya identify challenges that affect the reporting mechanism such as interference by the perpetrator and retaliation against the victims. The study concludes by putting forward possible recommendations for the improvement of the effectiveness of the reporting mechanism which include; increasing the avenues of reporting sexual harassment within the workplace, ratifying and domesticating the Convention against Violence and Harassment in the World of Work and providing a platform for complainants to openly discuss instances of sexual harassment. Much of the information gathered has been sourced from books, papers, case law and published journals.
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School